Firn Evolution at Camp Century, Greenland: 1966–2100 - Vandecrux, Baptiste; Colgan, William; Solgaard, Anne M.; Steffensen, Jørgen Peder; Karlsson, Nanna B. (Frontiers in Earth Science, 2021)
The abstract is not currently available. We kindly ask our readers to wait for the final typeset article to be published.